Remineralization of demineralized bone matrix in critical size cranial defects in rats: A 6‐month follow‐up study. Issue 7 (2nd July 2015) - Horváthy, Dénes B.; Vácz, Gabriella; Toró, Ildikó; Szabó, Tamás; May, Zoltán; Duarte, Miguel; Hornyák, István; Szabó, Bence T.; Dobó‐Nagy, Csaba; Doros, Attila; Lacza, Zsombor
Abstract: The key drawback of using demineralized bone matrix (DBM) is its low initial mechanical stability due to the severe depletion of mineral content. In the present study, we investigated the long‐term regeneration of DBM in a critical size bone defect model and investigated the remineralization after 6 months. Bone defects were created in the cranium of male Wistar rats which were filled with DBM or left empty as negative control. In vivo bone formation was monitored with computed tomography after 11, 19, and 26 weeks postoperatively. After 6 months, parietal bones were subjected to micro‐CT. Mineral content was determined with spectrophotometric analysis. After 11 weeks the DBM‐filled bone defects were completely closed, while empty defects were still open. Density of the DBM‐treated group increased significantly while the controls remained unchanged. Quantitative analysis by micro‐CT confirmed the in vivo results, bone volume/tissue volume was significantly lower in the controls than in the DBM group. The demineralization procedure depleted the key minerals of the bone to a very low level. Six months after implantation Ca, P, Na, Mg, Zn, and Cr contents were completely restored to the normal level, while K, Sr, and Mn were only partially restored. The remineralization process of DBM is largely complete by the 6th month after implantation in terms of bone density, structure, and key mineral levels. Although DBM does not provide sufficient sources for any of these minerals, it induces a faster and more complete regeneration process. © 2015 Wiley Periodicals, Inc. J Biomed Mater Res Part B: Appl Biomater, 104B: 1336–1342, 2016.